Growth, mortality and exploitation rate of Pampus argenteus, Parastromateus niger and Scomberomorus commerson in Sebatik Waters, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Salim G, Handayani KR, Indarjo A, Ransangan J, Atieqah N. 2020. Growth, mortality and exploitation rate of Pampus argenteus, Parastromateus niger and Scomberomorus commerson in Sebatik Waters, Indonesia. Biodiversitas 21: 5363-5372. The economic revenue of the local government of the Indonesian Sebatik Island relies much on the exploitation of its rich marine biodiversity. One of the important economic activities is the capture fisheries of commercially important fishes such as the white pomfret (Pampus argenteus) and black pomfret (Parastromateus niger), and mackerel fish (Scomberomorus commerson). The current study aims to estimate the growth, condition factor, and exploitation rate of the fish species for developing sustainable fishery management. Fish samplings were conducted in the Sebatik Waters, Nunukan District, North Kalimantan Province, Indonesia from June to July 2020. The fish were caught using gillnet at daytime (pomfrets) and nighttime (mackerel), respectively. Then, 82, 73, and 83 specimens of white pomfret, black pomfret, and mackerel were randomly selected for the length-weight relationship, condition factor, and exploitation rate analysis, respectively. The results revealed that the size distribution of the white pomfret population in the coastal waters of Sebatik Island ranged from 220.0 to 351.0 mm, black pomfret ranged from 231.0 to 362.0 mm and mackerel, ranged from 242.0 to 432.0 mm. All the fish species exhibited negative allometric (b50%) and fishing mortality (>60%) of all the fish species analyzed in this study indicate that there is a sign of overfishing to these fish resources in the coastal waters of Sebatik island. Hence, sustainable fishing management is timely needed to prevent depletion of these important fishery resources. Such management can include fishing restrictions for small-sized and first mature fish, close fishing season, and strict requirement for fishing permits.
Keywords: Fisheries management, overfishing, population, population depletion